Quality Management of Education in National Defense and Security Education Centers is Currently Prevalent - Chien, Duong Van; Loc, Hoang Xuan (VNU Journal of Science: Education Research, 2023)
Quality education management is a scientific practice encompassing administration and training across all educational levels. It is widely adopted in national academies and schools today, holding a crucial role in enhancing education quality. National Defense and Security Education Centers, part of higher education institutions, specialize in training and nurturing defense and security knowledge. These centers face unique challenges due to their large annual cohorts engaged in round-the-clock activities, studies, and training. As a result, education quality management is organized and implemented using suitable methods, receiving focused attention and guidance from center leadership. Sociological investigations indicate that 100% of these centers acknowledge the significant role of education quality management, with a strong impact on outcomes and training quality. Similarly, 100% of management staff and instructors believe in the positive effects of education quality management on enhancing training quality. Despite recognizing the importance of education quality management, practical implementation within National Defense and Security Education Centers reveals several limitations. Inadequate management tools, a predominant focus on learners' academic outcomes, and challenges related to input-output control and certification affect training quality. Hence, continuous research and innovative management approaches are essential for these centers to truly achieve desired education quality, contributing to the successful completion of their mission.